PWE-022 The incidence of coeliac disease in patients presenting with stress fracture to a tertiary centre. (June 2019) - Smith, R; Baldock, J; FitzPatrick, M; Jones, N; Newton, J
Abstract : Introduction: Stress fractures, fatigue-induced bone fractures caused by repetitive mechanical stress, are often multifactorial in nature and are associated with a number of metabolic bone disorders. Whilst the association between coeliac disease (CD) and osteoporosis is well-recognised, it is unclear whether an association between CD and stress fractures exists, with only rare case reports in the literature. This study aimed to examine the incidence of CD in a prospective cohort of patients presenting with stress fractures to a specialist NHS Sport and Exercise Medicine (SEM) clinic. Methods: An analysis of a prospective cohort of 100 consecutive patients with radiologically-proven stress fractures who presented to a single tertiary UK SEM clinic was performed. Electronic health records were used to examine fracture site, comorbidities, tissue transglutaminase (TTG) result, biochemistry, haematinics, dual energy x-ray absorptiometry, and endoscopy findings. Results: Seventy patients in the cohort were female (70%) and the mean age was 37 years (range 18–69). Two patients had pre-existing coeliac disease (2%). Coeliac serology was performed for 85 patients (85%), with 5 additional patients found to have a positive TTG (5% of cohort, 6% of those tested). CD was confirmed by endoscopic biopsy in three patients, with two not undergoing endoscopy locally due to their geographic location, giving a prevalence of CD in this cohort of 5–7%. The most common site of fracture was the metatarsals (5/7, 71%), with hallux sesamoid and fibula fractures detected in one patient each respectively. Six patients with possible or confirmed CD underwent DEXA. No patients had osteoporosis, with osteopenia (T-Score between -1.0 and -2.5) found in three patients (3/6, 50%). Coexistent vitamin and mineral deficiency were common in the CD patients (iron, 2/6 (33%); vitamin B12, 2/5 (40%); folate, 1/4 (25%); vitamin D, 2/6 (33%)). Conclusions: In this cohort of patients with stress fractures, the prevalence of CD was between 5% and 7%, approximately 5-fold higher than general UK population estimates. Screening for CD with serological testing should be considered in all patients presenting with stress fractures. Stress fractures were not associated with osteoporosis in the patients with CD, and only 50% had osteopenia, suggesting that coeliac disease and the associated malabsorption leads to stress fracture via mechanisms separate from reduced bone density.